2013
DOI: 10.3892/ijo.2013.2151
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor decreases CMYC and KRAS expression by upregulating let-7a expression in ER−, PR−, AR+ breast cancer

Abstract: It is generally known that the decision to use anti-estrogen therapy is based on the expression of estrogen and progesterone receptors in breast cancers. Recent studies have shown that androgen receptor (AR) is frequently expressed in ER-, PR- breast cancer and plays an important role in the prognosis of breast cancer patients. Furthermore, AR can increase the global expression of microRNAs, post-transcriptional gene regulators that play a crucial role in the initiation and progression of breast cancer. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 47 publications
4
43
1
Order By: Relevance
“…In addition, several recent studies showed that AR can indirectly regulate the expression and function of its target gene also via mechanisms involving miRNAs (Ma et al 2013, Lyu et al 2014, Mishra et al 2014, Pasqualini et al 2015. In this study, we found that miR-126* could decrease FSHR expression and increase the rate of apoptosis in pGCs by binding directly to the 3′-UTR of FSHR.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…In addition, several recent studies showed that AR can indirectly regulate the expression and function of its target gene also via mechanisms involving miRNAs (Ma et al 2013, Lyu et al 2014, Mishra et al 2014, Pasqualini et al 2015. In this study, we found that miR-126* could decrease FSHR expression and increase the rate of apoptosis in pGCs by binding directly to the 3′-UTR of FSHR.…”
Section: Discussionsupporting
confidence: 47%
“…A recent study demonstrated that androgens attenuate follicular atresia by increasing expression of miR-125b, which in turn suppresses the expression of proapoptotic proteins (Sen et al 2014). Several studies also showed that androgens and AR control their target genes by regulating the expression of miRNAs (Ma et al 2013, Lyu et al 2014, Pasqualini et al 2015. To date, however, the regulatory relationship between AR, miRNAs, and FSHR in GCs has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…The authors report that mRNA expression levels and KRAS amplification were increased significantly in metastatic compared with primary lesions consistent with involvement of KRAS alterations in disease progression (Birkeland et al 2012). In a recent study, KRAS protein expression was reported to be decreased by AR signalling in ERK, PRK and ARC breast cancer cells (Lyu et al 2014), which may indicate a further target for androgen therapy in EC.…”
Section: Endometrial Cancermentioning
confidence: 83%
“…However, it is currently unclear how to stratify individual breast cancers based on whether they will respond favourably to androgen treatment or not. In different breast cancer cell lines, modulation of androgen signalling can have growth-inhibitory or growth-promoting effects (Birrell et al 1995, Ortmann et al 2002, Greeve et al 2004, Lyu et al 2014, reviewed in Fioretti et al (2014), and this extends to the applicability of AR expression as a prognostic marker in specific subtypes of breast cancer (Kuenen-Boumeester et al 1996, Agoff et al 2003, Peters et al 2009, Kraus et al 2010, Gasparini et al 2014. Such conflicting reports/data raise concerns for the clinical efficacy of androgen modulation in breast cancer.…”
Section: Ar Expression In Mammary Epitheliummentioning
confidence: 99%